CONTRIBUTION TO THE ETHNO-BOTANICAL STUDY AND THE BIOENERGETIC, COSMETIC, AND PHARMACO-BIOLOGICAL VALORISATION OF J. CURCAS L. (EUPHORBIACEAE) IN THE DEMOCRATIC REPUBLIC OF THE CONGO - LIYONGO, Clément T.; Mbingu, Moïse L.; Masengo, Colette M.; Ngbolua, Jean-Paul; Mawunu , Monizi; Mawil , Clarisse F.; Kankolongo , Joséphine N.; Eyale , Louis E.; Dinangayi , Dorothée T.; Tshibangu , Damien S.; Mpiana, Pius T. (Science Journal of University of Zakho, 2023)
Jatropha curcas is a versatile plant with medicinal, energy, and cosmetic potential. The ethno-botanical survey was carried out using a stratified sampling technique. J. curcas oil was extracted using the standard method, while its characterization was carried out in accordance with Standard DIN 51605 for Rapeseed Oil Fuel. The antiviral activity was evaluated in silico using molecular docking. The study found that the majority of respondents were over 50 years old, with the leaves being the most used parts. Twenty-seven illnesses are treated, of which the 5 most treated are gastritis, cough, haemorrhoids, yellow fever, and tooth decay. The Budja and the Yaka are the only ones who reached a consensus on 6 illnesses. Physico-chemical analyses showed that J. curcas oil complies with the DIN V 51605 standard. The biodiesel obtained gave a better cetane number (109). Molecular modelling indicated that the oil inhibited 2 molecular targets involved in Monkeypox virus DNA replication. J. curcas is a plant with high medicinal, energy and cosmetic potential that should be exploited in the context of sustainable development. J. curcas can be a source of income for rural areas. Bio-clinical studies should therefore be carried out to validate the efficacy and safety of this plant in the treatment of diseases.